Se opp ! : Kunst fra Moskva og St. Petersburg = Watch Out : Art from Moscow and St. Petersburg - Andreeva, Ekaterina; Brandtzaeg, Karl J.; Degot, Ekaterina; Turkina, Olesya (Oslo : National Museum of Contemporary Art Oslo, 2004)
Blue Noses ; Chernysheva, Olga ; Dubossarsky, Vladimir ; Vinogradov, Alexander ; Gorlova, Lyudmila ; Kallima, Alexey ; Kulik, Oleg ; Osmolovsky, Anatoly ; Savko, Alexander ; Waldron, Ira ; Bugaev, Sergey Afrika ; Factory of Found Clothes ; Gurianov, Georgy ; Khlobystin, Andrei ; Kuznetsov, Viktor ; Maslov, Oleg ; Novikov, Timur ; Tobreluts, Olga ; Vilensky, Dmitry
biog., ind. tent., gr. tent. p. 104-109
Engels
Noors
Russisch
Exhibition. Watch Out ! Art from Moscow and St. Petersburg. National Museum of Contemporary Art Oslo, 27.05.2004 - 05.09.2004.
boek
Keywords: Moskou; St-Petersburg; Rusland